Influence of the variable stoping speed on the occurrence mechanism of rock burst - Wei-Yao Guo; Yue Qiu; Tong-bin Zhao; Yun-Liang Tan; Sheng Lan; Wen-Guo Chen (Geomatics, Natural Hazards & Risk, 2019)
Many field investigations have proven that the stoping speed of mining face is closely related to the amount of energy released from hard roof fracturing. Taking the Dongtan Coal Mine as the engineering background, we first analyze the relationship between the stoping speed and the microseismic activity. Then, the effect of the variable loading rate on the mechanical behavior of rock or coal is studied using PFC2D simulation. Finally, the occurrence mechanism of rock burst induced by the stoping speed variation under the hard roof condition is revealed. The stoping speed variation is not advantageous for the slow release of elastic energy stored in the roof and coal seam, and it can easily induce high energy events, which can reach 2.88–6.81 × 106 J. Under a variable loading rate condition, the energy storage capacity of coal and the released kinetic energy increase. When the stoping speed increases, the energy stored in the coal seam simultaneously increases, which implies that the dynamic balanced system is disturbed, and a rock burst may occur. When the stoping speed decreases, the new dynamic balanced system cannot absorb the entire pre-stored energy, and some of that energy will be released, which may also induce a rock burst.